Motivators and Barriers to Seeking Metabolic and Bariatric Surgery Among Adolescents: A Qualitative Study - Marlyn A. Allicock; Jackson M. Francis; Rashon Braxton; Dhatri Polavarapu; Maral Misserian; M. Sunil Mathew; Alicia Wheelington; Bethany R. Cartwright; Faisal G. Qureshi; Sarah E. Barlow; Sarah E. Messiah (Obesity Science & Practice)
ABSTRACT Background The prevalence of severe obesity among adolescents has increased the use of metabolic and bariatric surgery (MBS) as a therapeutic option. Understanding factors influencing adolescent MBS choice and the support needed to undergo MBS is crucial for improving health outcomes. This study examines the motivations and support needs of a diverse sample of adolescents seeking MBS via the patient voice. Methods Adolescents (n = 14) at a weight loss surgery clinic in a large academic healthcare system participated in qualitative interviews. Of the participants, 10 were female, 6 were non‐Hispanic Black, 3 were non‐Hispanic White, and 5 were Hispanic. Interviews were recorded, transcribed, and thematically analyzed. Results Three themes emerged: Intrinsic motivators, extrinsic motivators, and barriers. Intrinsic motivators include personal physical and mental health goals. Extrinsic motivators involved family and medical team support, which provided encouragement, validation, and perceived confidence for lifestyle changes. Additionally, observing family members who previously completed MBS was a significant extrinsic motivator. Concerns included fear of dying/complications from MBS, and possible weight regain post‐MBS. Conclusion Adolescent MBS programs should enhance intrinsic motivation for behavior changes. Findings highlight opportunities for bolstering support pre‐ and post‐MBS and addressing MBS‐related anxieties related to long‐term weight management.